The role of side effects in shifting patients from first line to second line ART at Nthabiseng Clinic in Soweto, Johannesburg - Pasipamire, Munyaradzi (My University, 2014)
The Human Immunodeficiency Virus (HIV) which causes Acquired Immunodeficiency Syndrome (AIDS) has caused a global scare with mainly poor African countries suffering the greatest burden. Treatment of HIV is more of palliation rather than cure such that there is no room for treatment interruption if treatment goals are to be met. Antiretroviral treatment is associated with short term and long term side effects which have the potential to negatively impact on the high levels of adherence to treatment that is required to maintain virological suppression and may eventually lead to development of drug resistance and treatment failure. This research aims to identify the extent to which these side effects, through possible poor adherence, impact on treatment successes by measuring the risk that side effects contribute towards treatment failure. Methods Secondary data analysis was conducted on a cohort of patients who initiated ART between 2004 and 2010 at a large tertiary facility in Johannesburg. Patients who were switched to second line ART due to treatment failure were identified. Assessment of side effects on adherence was done. The hazards of side effects among patients switching and not switching to second line were calculated using Cox proportional hazards regression adjusting for other socio-demographic and clinical predictors for treatment failure. Interaction between side effects, gender, age and that of side effects and adherence was investigated. Time dependent covariates were also investigated. Confounding was controlled using multivariate Cox regression analysis. Results There were 5285 patients in the baseline cohort with multiple entry points who contributed 16035 person-years of follow up. The cohort consisted of 63.2% females and 36.8% males. Of these 85.9% were initiated on stavudine (d4T)- based regimen, 7.1% on tenofovir (TDF), 6.3% on zidovudine (AZT)-based regimen and 0.7% on other regimens. The median and mean time at risk per subject was 2.2 and 2.3 years respectively. A total of 770 episodes of side effects due to first line ART were experienced with some patients recording multiple side effects at different time points. Adherence data were found to be missing and incoherent in some of the regimen dosages and could not be used to objectively compare patients. There were 430 patients who were switched to second line ART due to treatment failure. Relative to the group of no side effects, the adjusted hazard ratios for mild, moderate and severe side effects were 1.40 (95% CI=0.94-2.09) p=0.10; 1.72 (95% CI=1.35-2.20) p<0.01 and 1.24 (95% CI=0.65-2.35) p=0.52 respectively. Therefore, overally side effects did not seem to play a role in the time to switch to second line ART. Sex, baseline CD4 cell count, the period during which ART was initiated and the time between date of testing HIV positive and date of initiating were significantly associated with the time to switching to second line ART. Conclusion The study informs that side effects overally may not play a significant role in switching patients from first line to second line ART with the exception of moderate side effects. However, patients who experience side effects should be closely monitored and adequately counselled to help them cope with the side effects so that optimal adherence levels are maintained. Availability of adherence scores or additional information on pills that should have been taken on periods during which pills were reported to have been missed would have made the research more valuable by allowing objective comparison of adherence among patients.
Keywords: Acquired Immunodeficiency Syndrome|; Antiretroviral Therapy, Highly Active; HIV-1